Age, geochemistry, and origin of the mid-Proterozoic Häme mafic dyke swarm, southern Finland - Luttinen, Arto; Lehtonen, Elina; Bohm, Katja; Lindholm, Tanja Marjukka; Söderlund, Ulf; Salminen, Johanna (Bulletin of the Geological Society of Finland, 2022)
We have reappraised the age and composition of the mid-Proterozoic Häme dyke swarm in southern Finland. The dominant trend of the dykes of this swarm is NW to WNW. Petrographic observations and geochemical data indicate uniform, tholeiitic low- Mg parental magmas for all of the dykes. Nevertheless, the variability in incompatible trace element ratios, such as Zr/Y and La/Nb, provides evidence of changing mantle melting conditions and variable crustal contamination. Our ID-TIMS 207Pb/206Pb ages for four low-Zr/Y-type dykes indicate emplacement at 1639 ± 3 Ma, whereas the most reliable previously published ages suggest emplacement of the high-Zr/Y-type dykes at 1642 ± 2 Ma. We propose that the Häme dyke swarm, and possibly also the other mid- Proterozoic mafic dyke swarms in southern Finland, records a progressive decrease in Zr/Y values due to magma generation under developing areas of thinned lithosphere. We consider that the formation of mafic magmas was most probably associated with the upwelling of hot convective mantle in an extensional setting possibly related to the nearby Gothian orogeny. The generation of tholeiitic magmas below continental lithosphere was probably promoted by the elevated mantle temperature underneath the Nuna supercontinent. We speculate that the origin of most of the relatively small mid-Proterozoic mafic dyke swarms, anorthosites, rapakivi granites, and associated rocks found across Nuna was similarly triggered by extensional plate tectonics and the convection of anomalous hot upper mantle below the supercontinent. Peer reviewed